Avaliação do modelo de status epilepticus por ouabaína: da administração intracerebroventricular à análise de parâmetros comportamentais e indicadores de dano cerebral - Lustosa, Ítalo Rosal (2016)
Status epilepticus (SE) is a common and potentially lethal form of clinical emergency. The advances in antiepileptic therapy in the last decades failed to change the rates of treatment responsiveness in that condition, as well as in epilepsies. Down regulation of Na +, K + -ATPase (NKA) activity has been implicated in the pathophysiology of various neurodegenerative diseases, including epilepsy. In the present study, epileptic seizures were induced through intracerebroventricular (i.c.v.) ouabain, a model with predictive value for generalized tonic-clonic seizures. The ethological characteristics of the seizures were outlined regarding the localizing semiology. Neurochemical analysis were also performed: lipoperoxidation, TBARS; reduced glutathione (GSH) concentration; and nitrite (NO2-) concentration in prefrontal cortex (F), hippocampus (H), striatum (E), thalamus (T) and mesencephalon (M). About ~ 85% of the animals receiving 29.23 μg of i.c.v. ouabain exhibited a behavior consisting of two procursive seizures intercalated by freezing and followed by partial clonus evolving as generalized clonus with loss of the righting reflex and late tonus. This pattern is highly suggestive of primary multifocal ictogenesis in limbic (H) and brainstem (lower colliculus) areas followed by secondary generalization. Lipoperoxidation was significantly increased in relation to control in all studied areas: F, E and H (p <0.0001); T (p <0.001); M (p <0.01). GSH concentration was significantly reduced only in F (p <0.01) and E (p <0.0001). NO2- concentration was increased in T and M (p <0.01); Values of p <0.05 were considered significant. Neurochemistry evidences severe oxidative damage, mainly in lipid membranes. The increase in NO2- in caudal structures corroborates with literature about the audiogenic model. A hypothesis that may aggregate pathomechanistic relevance to the model as theoretical construct is thrown. Furthermore, the implementation of an i.c.v administration protocol offers ample possibilities for the research and drug development.